Food processing and preservation : laboratory manual - Wan Kamarudin, Wan Saidatul Syida; MN Azmi, Aida Firdaus; Ahmad, So'bah; Ramli, Siti Suhara (Penerbit UiTM (UiTM Press), 2025)
In today's market, there is a wide array of food items crafted by food producers to meet consumer demands. Transforming these plant and animal-derived materials into consumable food products poses a formidable challenge for food manufacturers as they endeavour to preserve the nutritional content and overall quality of the end product. Consequently, it is crucial to grasp the principles and methodologies applied during the processing of these raw materials into edible goods. The aim of this laboratory manual is to acquaint students with the various methodologies employed in the fields of food processing and preservation. Food processing involves the transformation of plant or animal-derived materials into consumable goods like jams, canned products, sausages, and baked items. Conversely, food preservation encompasses techniques for treating and managing food to regulate, minimise, or eradicate microorganisms, thereby preserving and extending the shelf life of food items. These two procedures encompass a variety of approaches, including the incorporation of chemical additives, drying, crystallisation, sugaring, and fermentation. The amalgamation of these methodologies results in the production of food products that exhibit improved quality concerning nutritional properties and sensory attributes. This manual includes seven food preservation and manufacturing experiments to teach students methods, practical skills, and reporting. It aims to enhance students' selfsustainability and entrepreneurship skills.